Project-based instructional design for computer education an experience - Concepcion, Marie Joan O. (2005)
Project-Based Learning as an approach lacks a universally-accepted model or theory. This study sought to incorporate the latest thinking on standards and assessment to outline a structured PBL model that teachers can adapt and implement in the classroom. Document analysis was done to identify patterns, commonality, strengths, and weaknesses of the Project-Based Instructional Design. Primary sources of data were the Computer Education syllabus, project proposal, progress reports, software evaluation tools, reflection papers, and test rubrics of 13 groups in second year high school in a private Catholic school. Results showed significant changes in knowledge, skills, and attitudes of students throughout the PBID process. Thus, the implemented PBID is an appropriate instructional design for secondary computer education.
Thesis (M.A. Curriculum Studies)--University of the Philippines, Diliman.
Keywords: Computer-assisted instruction -- Philippines -- San Juan (Metro Manila); Instructional systems -- Philippines -- San Juan (Metro Manila); Educational technology -- Philippines -- San Juan (Metro Manila)